Composition of Fatty Acid and Identification of Lauric Acid Position in Coconut and Palm Kernel Oils - Silalahi, Jansen; Lida Karo Karo; Sinaga, Siti Morin; Yosy Cinthya Eriwaty Silalahi (Indonesian Journal of Pharmaceutical and Clinical Research, 2018)
The nutritional value and biochemical properties of oil are measured by the fatty acids composition in oil and the position of fatty acids (sn-1,2,3) in the triacylglycerol (TAG) molecule. The purpose of this study was to measure the nutritional value based on the fatty acids composition of virgin coconut oil (VCO) and palm kernel oil (PKO), and the position of lauric acid in sn-2. The VCO used was VCO obtained from one of the Pharmacies store in Medan, and PKO from the Oil Processing Plant. The total fatty acid composition was measured by Gas Chromatography. The nutritional value of fat was evaluated by the percentage deviation from 33.33% (ratio: 1: 1: 1) of each group of fatty acid (saturated fatty acids; SFA: monounsaturated fatty acids; MUFA:polyunsaturated fatty acid (PUFA). The distribution of lauric acid in TAG was conducted through hydrolysis by using specific lipase enzymes active at sn-1,3 positions, so that free fatty acids and 2-monoacylglycerol were produced from one TAG molecule. Then free fatty acids were determined by Gas Chromatography. The distribution of lauric acid at sn-2 position was the difference between total lauric acid on TAG before hydrolysis and free lauric acid from sn-1.3 position after hydrolysis. The results showed that PKO nutritional value was better because of the smaller deviation (95.29%) compared with nutritional value of VCO with a greater deviation (118.55%). Lauric acid in sn-2 from VCO and PKO showed that the distribution of lauric acid in sn-2 position was not different,48.33and 48.59%. Keywords: virgin coconut oil, palm kernel oil, composition of fatty acids, sn-2 position, lauric acids